DOI: 10.4018/978-1-60566-830-7.ch006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Individual Learner Differences and Success in the Online Learning Environments

Abstract: “Education over the Internet will be the next big killer application,” says John Chambers, President and CEO of Cisco Systems. He also states that online learning will be much bigger than the last killer application of the Internet — e-mail (Friedman, 1999). The recent surge in online learning has opened up the eyes of many educators to the growing possibilities of online learning and teaching. As these online offerings continue to grow, the educational impact will have far reaching implications for schools, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…According to Pintrich, Smith, Garcia and McKeachie (1993), learning strategies consist of three categories and nine subordinates. Colorado and Howell (2009) summarized a detailed description of each component as follows:…”
Section: Learning Strategiesmentioning
confidence: 99%
“…According to Pintrich, Smith, Garcia and McKeachie (1993), learning strategies consist of three categories and nine subordinates. Colorado and Howell (2009) summarized a detailed description of each component as follows:…”
Section: Learning Strategiesmentioning
confidence: 99%
“…Younger students also struggled more than mature students to adapt to online environments (Xu and Jaggars, 2013). Several factors are shown to contribute to this view, as a result of age increase, for instance, elaboration, critical thinking and metacognitive self-regulation (Colorado and Eberle, 2010). Montgomery and Groat (1998) infer those mature students having life experiences are more inclined to be independent learners.…”
Section: Multi-group Analysismentioning
confidence: 99%
“…It is important to know demographic characteristics (age, gender, attended classes, grades awarded and academic achievement) for understanding engagement of students in learning environment and relationship between IA and FoMO. When the literature is examined, studies are found to address relationship between engagement in online learning environment and demographic characteristics such as age, gender and ethnicity (Colorado and Eberle, 2010;Hamby, 2015;Ke and Xie, 2009;Schneider and Germann, 1999;Teoh et al, 2013;Yoo and Huang, 2013). When the results of the relevant studies are examined, it is seen that different findings are obtained in the matter of effect of age and gender on engagement in learning environment.…”
Section: Students' Demographic Characteristics As Predictor Of Se Fom...mentioning
confidence: 99%
“…Studies reveal that there is a positive relationship between academic achievement of students with engagement in online learning environments (Colorado and Eberle, 2010;Alt, 2015;Lei et al, 2018;Zhang et al, 2018). In this case, demographic characteristics which affect academic achievement may also affect engagement of students in learning environments.…”
Section: Students' Demographic Characteristics As Predictor Of Se Fom...mentioning
confidence: 99%
See 1 more Smart Citation